Case Series of Rare Primary Intranasal Diffuse Large B-cell Lymphoma among Filipinos - Pizarro, Dean Marvin Potato; Cruz-Ordinario, Mel Valerie; Butalid, Vivian; Belle Francia, Marie (Asian Pacific Journal of Cancer Care, 2022)
Background: Diffuse Large B-cell Lymphoma (DLBCL) is the most common type of Non-Hodgkin Lymphoma (NHL) at the present time. However, it rarely presents in the intranasal cavity as the primary site. There is scarcity of local data on this disease, and the outcomes to the standard treatment are still unclear. Objective: In this case series, we presented 2 patients with primary intranasal DLBCL that were treated with chemotherapy ± anti-CD20 antibody and radiotherapy. Results: Both cases were in the early stage of disease. One patient was given systemic chemotherapy (CHOP) plus anti-CD20 antibody (Rituximab), and the other patient was only given chemotherapy (CHOP) due to financial constraints. The systemic treatment was followed by Involved-Field Radiotherapy (IFRT). Both patients demonstrated with an objective radiologic and clinical response to the treatment. The patients had no evidence of disease recurrence at 36 months. Conclusion: The cases presented showed that primary intranasal DLBCL appears to have an objective and durable response to the treatment for DLBCL as prescribed by the guidelines. The findings in this study can be added to the pool of data to expand our comprehension of this disease process.